Farmer management of government irrigation systems: a viable option for Africa's smallholders? - Shah, Tushaar; van Koppen, Barbara; Merrey, Douglas J.; Lange, M. de; Samad, M. (2001)
This research assesses the widespread transfer of government-run smallholder irrigation schemes in Africa to the management of organized groups of farmers in the light of decades of experience by various countries . The comparative study of the Irrigation Management Transfer (IMT) suggests that it can work if certain preconditions are met. This research finds that IMT is unlikely to work for African smallholders. Here, the institutional alternatives most likely to succeed are those that address the whole complex set of constraints that African smallholders face.